Effects of nonlinearity on determination of bolt forces for the operational state of a bolted flange connection - Grzejda, Rafał (Zielona Góra: Uniwersytet Zielonogórski)
Modelling and calculations of an asymmetrical bolted flange connection at the operational stage are presented. The physical model of the joint is based on a flexible flange element that is connected with a rigid support by means of hybrid elements, which substitute bolts. Between the flange element and the support, the linear Winkler model of a contact layer is taken into account. The bolted flange connection is preloaded and then subjected to an eccentric normal load. The influence of nonlinearity of the contact layer between the joined elements on computational values of bolt forces has been investigated. Results of calculations for several different values of the joined element?s thickness are described.
Keywords: bolted flange connection; operational state; bolt force